Physical Inactivity and Mortality Risk - Peter Kokkinos; Helen Sheriff; Raya Kheirbek (Cardiology Research and Practice)
In recent years a plethora of epidemiologic evidence accumulated supports a strong, independent and inverse, association between physical activity and the fitness status of an individual and mortality in apparently healthy individuals and diseased populations. These health benefits are realized at relatively low fitness levels and increase with higher physical activity patterns or fitness status in a dose-response fashion. The risk reduction is at least in part attributed to the favorable effect of exercise or physical activity on the cardiovascular risk factors, namely, blood pressure, diabetes mellitus and obesity. In this review, we examine evidence from epidemiologic and interventional studies in support of the association between exercise and physical activity and health. In addition, we present the exercise effects on the aforementioned risk factors. Finally, we include select dietary approaches and their impact on risk factors and overall mortality risk.